Predominate weed flora in summer rice as influenced by methods of establishment and weed management practices - A.M. Rathod,; T. U. Patel,; Saleha Diwan,; R. P. Vaja, (The Bioscan, 2025)
A field experiment was conducted at the College Farm of Navsari Agricultural University, Navsari (Gujarat), during the summer seasons of 2019-20 and 2020-21. The experiment was arranged in a split-plot design with four replications. Three crop establishment methods were tested in the main plots: S1 - Direct Seeded Rice, S2 - Conventional Transplanted Rice, and S3 - Sprouted Seed (line sowing). Five weed management practices were evaluated in sub-plots within each main plot: W1 - Weedy check (control), W2 - Hand weeding twice at 20 and 40 DAS/T, W3 - Pretilachlor 50% EC 1000 g ai/ha (pre-emergence) followed by Bispyribac sodium 10% SC 25 g ai/ha at 30 DAS/T, W4 - Pyrazosulfuron-ethyl 10% WP 15 g ai/ha (pre-emergence) followed by Bispyribac sodium 10% SC 25 g ai/ha at 30 DAS/T, and W5 - Pretilachlor 50% EC 1000 g ai/ha (pre-emergence) followed by Chlorimuron ethyl + Metsulfuron methyl 20% WP 4 g ai/ha at 30 DAS/T. The rice cultivar used was NAUR-1. Echinochloa colonum L., Echinochloa crusgalli L., Cynodon dactylon L., Eragrostis minor L., Digitaria sanguinalis L., Dinebra retroflexa (Vahl) Panzer, Brachiaria ramose L. and Dactyloctenium aegyptium L. among the grasses; Cyperus rotundus L., Cyperus difformis L., Fimbristylis miliacea L. and Cyprus iria L. among the sedges and Alternanthera sessilis L., Marsilea quadrifolia L., Commelina benghalensis L. Phyllanthus niruri L., Euphorbia hirta L., Portulaca oleracea L, Tridax procumbens L., Physalis minima L. and Digera arvensis L. among the broad-leaved weeds, were the major weed species found from the experimental filed during both the seasons of experiment. Among methods of establishment, in direct seeded rice, the grasses weed specie are: Echinochloa colona L. and Echinochloa crus-galli L., broad leaved weeds are: Phyllanthus niruri L. and Alternanthera sessilis whereas Cyperus rotundus L and Cyperus difformis L. amongst sedge, found dominanat. In conventional transplanted rice, Echinochloa colona L., Digitaria sanguinalis L. and Dactyloctenium aegyptium L. were found dominant during among grasses weeds. Midst broad leaved weeds, Phyllanthus niruri L. found relatively superior and in case of sedges, Cyperus rotundus L. found superior during both seasons of experiment.